Timing factors in equestrian performance - Arundel, S.; Holmes, L. (World Congress of Performance Analysis of Sport IX, 2012)
Performance analysis research of show jumping is sparse, despite the use of such technology within British Equestrian since 2002 (British Eventing, 2007). Understanding the factors that contribute to success in show jumping is essential when preparing the horse and rider combination for performance. As competition levels progress, the complexity of the courses constructed increases, putting a greater significance towards the understanding of optimal approach strategies. The aim of the current study was to investigate whether optimal riding strategies can be identified via the use of performance analysis techniques during the show jumping course of a British Eventing event. Seventy six (n=76) competitors were analysed with angle of approach to the fence, the number of strides within the direct route before the fence, and the ground times between each fence recorded. Results data were grouped between competitors of successful clearance rounds (n=27) and those that obtained faults (n=49). Nine of the 14 split times and 10 of the 14 cumulative round times were normally distributed according to Kolmogorov-Smirnov tests (p > 0.05). Therefore, nonparametric procedures were applied. A series of Mann-Whitney U tests compared the split times and cumulative round times to each fence between competitors with clear rounds and those who obtained faults. Further Mann-Whitney U tests were used to compare the split times and cumulative round times to each fence between the competitors who cleared individual fences and those who did not. Mann-Whitney U tests were also used to compare the steps taken after turning into a fence between competitors who faulted and those who cleared for the 7 fences that followed curves in the course. The 6.14±0.45s split time to the final fence by those with clear rounds was significantly shorter than the 6.46±0.58s for those with faults (p = 0.015). The fifth fence was the second fence of a double jump. The 0.56±0.01s split time to this fence by the 3 competitors who faulted at the fence was significantly longer than the 0.48±0.08s for the 73 who cleared it. There were no other significant differences found in the timings (p > 0.05). No significant differences were found between the number of steps taken to any of the fences following curves between competitors clearing and faulting at those fences (p > 0.05). Timing data showed controversial evidence to the effectiveness on success in show jumping events. The current study has allowed an insight into the strategies that could be developed to help competitors establish specific training methods to improve their individual rate of success to move through the levels of British Eventing,